Cerebellar re-irradiation after whole brain radiotherapy significant symptom relief with minimal toxicity in metastatic brain patients - Ory Haisraely; Marcia Jaffe; Yaacov Richard Lawerence; Alicia Talianksy; Alicia Taliansky (Scientific Reports)
Abstract Whole-brain radiotherapy (WBRT) remains a standard treatment for extensive brain metastases, providing symptom relief and improved progression-free survival (PFS). Re-irradiation is often necessary for recurrent disease, particularly in the cerebellum, which accounts for 10–20% of cases. Cerebellar metastases are associated with distinct symptoms and poorer prognoses compared to supratentorial lesions. This study evaluates the outcomes of cerebellar-only re-irradiation for brain metastases, with or without stereotactic radiosurgery (SRS) for supratentorial lesions. A retrospective analysis of 56 patients treated between 2017 and 2023 was conducted. Patients received cerebellar-only re-irradiation after WBRT. Symptom improvement was assessed three months post-treatment. Statistical analyses included t-tests, Mann-Whitney U tests, and multivariable logistic regression. The cohort’s median age was 53 years, with breast cancer being the most prevalent histology (71%). Symptom improvement occurred in 75% of patients, with relief rates of 84.6% for nausea, 80% for headache, and 58.3% for dizziness. Dexamethasone use decreased in 76.3% of cases. Median PFS was 39.2%, with a six-month overall survival of 50%. Only 1.7% of patients developed symptomatic radiation necrosis. Factors associated with symptom improvement included younger age, extended intervals between WBRT and re-irradiation, and higher equivalent dose in 2 Gy fractions (EQD2). Cerebellar-only re-irradiation is an effective, low-toxicity option for recurrent cerebellar metastases. This approach warrants further validation in prospective studies, particularly in comparison to SRS.